A Post Bellum Paradox: Net Nutrition Variation by Socioeconomic Status, Gender and Race in the Late 19th Century - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2024)
When traditional measures for material conditions are scarce or unreliable, body mass, height, and weight are complements to standard income and wealth measures. A persistent question in welfare studies is the 19th century's 2nd and 3rd quarter's stature diminution, a pattern known as the antebellum paradox. However, the question may not be well stated nor experienced equally by women and non-white male samples. The late 19th century's political Granger, Greenback, and Populist movements may have affected farmer and non-farmer's net nutrition. Despite 19th and early 20th century US political movements, farmers had greater BMIs, taller statures, and heavier weights than non-farmers. From the 1870s through 1890s, women's body mass, height, and weight increased relative to men. Darker complexioned individuals had heavier weights and greater BMIs than their taller, fairer complexioned European counterparts, indicating that the traditional antebellum paradox needs to include women and non-European males and weight measures.
Keywords: C10; C40; D10; I10; N30; 330; gender; race; stature variation; cumulative net nutrition; nativity